Pengembangan LKPD IPA Berbasis Sains, Teknologi, Masyarakat, (STM) Untuk Meningkatkan Hasil Belajar Kognitif Siswa Kelas IV - Yebby Yelita Sari; Irwan Koto; Endang Widi Winarni (Jurnal Kajian Pendidikan Dasar, 2024)
This research aims to produce, describe and analyze the development of STM-based science LKPD to improve the cognitive learning outcomes of fourth grade students. In science learning, students are only given verbal explanations, resulting in abstract material. Problems arise because schools use LKPD which do not meet the scope of the learning objectives, because the weakness of the LKPD used so far, specifically natural resource material, is not in accordance with the demands of KD. 3.5 and KD 4.5. The research used in this study used research and development (R&D) data collection techniques in this study interviews, questionnaires, tests and documentation. The research instruments in this study were validation sheets, interview guidelines and document analysis sheets, questionnaires, test sheets, data analysis techniques in this study were qualitative and quantitative descriptive data analysis. The STM-based LKPD teaching materials that were developed were printed teaching materials that were made systematically according to the needs of students at school. The LKPD developed has a title, study instructions, basic competencies (pkok material), supporting information as well as tasks and work steps. The use of STM-based LKPD teaching materials is quite effective because the results obtained from the control class are 0.1600 or 15.9979% moderate. Meanwhile, the N-gain score for the experimental class is 0.3376 or 33.7569%, including the medium category.